Perkembangan Anak Tikus (F1) Asal Induk Penerima Asam Valproat sebagai Model Diabetes Mellitus - HADI SUNARYO; WASMEN MANALU; ADI WINARTO; BAMBANG KIRANADI (Fakultas Farmasi Universitas Pancasila, 2014)
To do research and development of antidiabetic drugs, animal models of diabetes in accordance with the conditions is required. The aim of this research was to develop a diabetic model that is fit to the pathophysiology of diabetic condition. The pregnant female rats were divided into 2 groups, one group was orally treated by a single dose of valproic acid (250 mg/kg bw) on day 9th of pregnancy and the other was a control. At the ages of 8, 16 and 24 weeks the blood samples of litters (F1) were taken for glucose, insulin and triglyceride determination. At the same time, pancreatic tissues were collected under deep anesthetic condition for immunohistological study. Results of blood glucose concentrations and histological finding of litters (F1) indicated that at the age of 8 weeks both had showed a similar pattern as compared to control. At the ages of 16 and 24 weeks, blood glucose and insulin level showed a significant increase, while positive insulin cells slightly decreased in number. It can be concluded that treating rat with valproic acid on days 9 of gestation will inhibit pancreatic β cells function. There is an indication that F1 of valproic acid treated pregnant mother start showing a metabolic syndrome at 16 weeks and being pronounce by aging.